Defect size dependence on threshold stress intensity for high‐strength steel with internal hydrogen. Issue 9 (19th July 2013) - Murakami, Y.; Matsunaga, H.; Abyazi, A.; Fukushima, Y.; Susmel, L.; Iacoviello, F.; Ferro, G.
ABSTRACT A series of tensile tests were carried out using hydrogen‐precharged specimens of SAE52100. Two types of tensile specimens were used: (i) smooth specimens and (ii) specimens having various shapes of artificial defects with sizes of about 35–500 µm. In the smooth specimens, fracture origins were non‐metallic inclusions with the size of 10–30 µm (e.g. Al2O3∙(CaO)x, TiN and TiC). In both types of specimens, hydrogen charging drastically decreased the tensile strength. The fracture toughness determined for the small defects at the fracture origin, that is, the threshold stress intensity KTH calculated from the defect size <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg2pqc8731" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />area</alternatives> and the applied tensile stress at the failure of the specimen σf, showed a defect size dependence, where area denotes the area of the domain defined by projecting the defect on a plane normal to the cylindrical axis of the specimen. Namely, the threshold value was reduced with a decrease in the defect size, which is similar to the crack size dependence in the ΔKth for small fatigue crack. The values of KTH for both the non‐metallic inclusions and artificial defects were much smaller than those for large cracks measured by the standard WOL (Wedge Opening Load) and CT (Compact Tension) specimens.